THE IMPACT OF PRINCIPAL SUPERVISION, DECISION-MAKING, AND JOB SATISFACTION ON JUNIOR HIGH SCHOOL TEACHERS' PERFORMANCE IN KOTA JUANG DISTRICT, BIREUEN REGENCY - Murhani, Murhani; Bahri, Saiful; Munawar, Munawar (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to analyze the influence of principal supervision, principal decision-making, and job satisfaction on teacher performance at junior high schools in Kota Juang District, Bireuen Regency. The research employed a quantitative approach using path analysis techniques. The sample consisted of 161 junior high school teachers, selected through a total sampling method. Data were collected through questionnaires. The results showed that principal supervision had a direct effect on principal decision-making with a t-value of 3.855, significance of 0.000, and beta coefficient of 0.293. It also had a direct effect on job satisfaction with a t-value of 4.107, significance of 0.000, and beta of 0.314. The direct effect of principal supervision on teacher performance was t = 3.199, significance = 0.002, and beta = 0.245. Principal decision-making had a significant effect on teacher performance with a t-value of 3.258, significance of 0.001, and beta = 0.241. Job satisfaction also significantly influenced teacher performance with a t-value of 5.195, significance of 0.000, and beta = 0.366. Indirectly, principal supervision affected teacher performance through decision-making (indirect effect = 0.071) and through job satisfaction (indirect effect = 0.115). Simultaneously, the three independent variables significantly influenced teacher performance with an F-value of 62.715 and a significance level of 0.000. These findings indicate that teacher performance improvement is not solely dependent on individual capabilities, but also highly influenced by effective principal supervision, participatory decision-making processes, and a high level of job satisfaction within the school environment